Faktor-faktor yang Berhubungan Tingkat Kecemasan Pasien Pre Operasi - Andan Peristika Didayana; Ah. Yusuf; Moch Bahrudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the factors associated with preoperative patient anxiety. The method used is a correlation descriptive design with a cross-sectional approach. The results showed that there was no significant relationship in terms of age (p=0.917), gender (p=0.366), education (p=495), occupation (p=945), and frequency of operations (p=262). This is because anxiety is the patient's self-response in response to the possibility that will occur if surgery is performed to improve the quality of nursing services and the effectiveness of providing nursing care to patients who will undergo surgery by providing education and health information. In conclusion, all patients undergoing surgery have different anxiety levels, which cannot be related to the patient's characteristics. This is because anxiety is the patient's self-response in response to the possibility that will occur if surgery is performed. Keywords: Frequency of Operations, Anxiety, Operations, Patients, Pre Operations